Individual, family, and culture level contributions to child physical abuse and neglect: A longitudinal study in nine countries - Lansford, Jennifer E (Archīum Ateneo, 2015)
This study advances understanding of predictors of child abuse and neglect at multiple levels of influence. Mothers, fathers, and children (N = 1,418 families, M age of children = 8.29 years) were interviewed annually in three waves in 13 cultural groups in nine countries (China, Colombia, Italy, Jordan, Kenya, Philippines, Sweden, Thailand, and the United States). Multilevel models were estimated to examine predictors of (a) within-family differences across the three time points, (b) between-family within-culture differences, and (c) between-cultural group differences in mothers' and fathers' reports of corporal punishment and children's reports of their parents' neglect. These analyses addressed to what extent mothers' and fathers' use of corporal punishment and children's perceptions of their parents' neglect were predicted by parents' belief in the necessity of using corporal punishment, parents' perception of the normativeness of corporal punishment in their community, parents' progressive parenting attitudes, parents' endorsement of aggression, parents' education, children's externalizing problems, and children's internalizing problems at each of the three levels. Individual-level predictors (especially child externalizing behaviors) as well as cultural-level predictors (especially normativeness of corporal punishment in the community) predicted corporal punishment and neglect. Findings are framed in an international context that considers how abuse and neglect are defined by the global community and how countries have attempted to prevent abuse and neglect.